Analisis Pendapatan Usahatani Padi Sawah Di Desa Tumani Kecamatan Maesaan Kabupaten Minahasa Selatan - Moonik, Engelie Marlin; Talumingan, Celcius; Lolowang, Tommy Fredy (AGRI-SOSIOEKONOMI, 2023)
This research aims to find out how much or how low the costs, receipts and income of lowland rice farmers in Tumani Village, Maesaan District are and to find out what problems lowland rice farmers face in running their business. This research was carried out for 3 months, namely from July 2022 to September 2022. This research used 2 types of data, namely primary and secondary data. Primary data was collected through direct interviews with respondents using a list of questions and secondary data was obtained from various sources related to the required data such as the Tumani Village office, the Maesaan District BPP Office, and even scientific writing. Sampling in this research used the method (Simple Random Sampling) or simple random. The number of farmers was 34 farmers and the respondents studied were 10 people or 30 percent of the total respondents. The data analysis used is quantitative descriptive analysis in determining production costs, revenue and R/C. Based on the results of research on lowland rice farming in Tumani Village, it is different. The amount of income received by farmers depends on the area of land owned by the farmer and whether rice farming in Tumani Village is feasible or profitable. We can see this from the results of the R/C analysis, namely 3.95, which means more than 1 and the average income of all respondent farmers in Tumani Village is IDR 19.289.769.